2008
DOI: 10.1021/jm800174p
|View full text |Cite
|
Sign up to set email alerts
|

Induced Association of μ Opioid (MOP) and Type 2 Cholecystokinin (CCK2) Receptors by Novel Bivalent Ligands

Abstract: Both mu opioid (MOP) † and type 2 cholecystokinin (CCK 2 ) receptors are present in areas of the central nervous system that are involved in modulation of pain processing. We conducted bioluminescence resonance energy transfer (BRET) studies on COS cells coexpressing MOP and CCK 2 receptors to determine whether receptor heterodimerization is involved in such modulation. These studies revealed the absence of constitutive or monovalent ligand-induced heterodimerization. Heterodimerization of MOP and CCK 2 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 61 publications
2
75
0
Order By: Relevance
“…57 On another hand, peripheral nerve injury causes a marked increase of CCK levels in DRG neurons. 24 Considering the ''anti-opioid'' role described for CCK, 37,41,58,59 the possibility exists that in injured tissues, including the cornea, increased CCK levels antagonize peripheral opioid receptors, thus counteracting the inhibitory effects of peripheral opioids on nociceptor sensitization during inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…57 On another hand, peripheral nerve injury causes a marked increase of CCK levels in DRG neurons. 24 Considering the ''anti-opioid'' role described for CCK, 37,41,58,59 the possibility exists that in injured tissues, including the cornea, increased CCK levels antagonize peripheral opioid receptors, thus counteracting the inhibitory effects of peripheral opioids on nociceptor sensitization during inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that μ-opioid and CCK2 receptors do not form constitutive heteromers when overexpressed in Chinese hamster ovary (CHO) cells, but can be induced to form heteromers in the presence of a bivalent ligand containing μ-agonist and CCK antagonist pharmacophores (25). Thus, heteromerization does not appear to be an artifact related to receptor overexpression in cultured cells.…”
mentioning
confidence: 99%
“…Recently, to investigate the possible existence of heterodimeric m opioid/ CCK 2 receptors, which may be responsible for the pharmacological observations mentioned above, the twin drugs 71 and 72 possessing the m agonist oxymorphone (45) [71] and the CCK 2 antagonist L-365,260 (70) [150] with spacers of various lengths were designed (Fig. 16) [151]. From the bioluminescence resonance energy transfer (BRET) studies [152], it is suggested that the m opioid receptor and the CCK 2 receptor would form homodimers in the COS cells.…”
Section: Opioid and Cholecystokinin Pharmacophoresmentioning
confidence: 99%